Ion acoustic cnoidal waves in a magnetized plasma in the presence of ion pressure anisotropy - Khalid, Muhammad; Rahman, Ata-ur (Astrophysics and space science, 2019)
An investigation of the ion acoustic nonlinear periodic (cnoidal) waves in a magnetized plasma with positive ions having anisotropic thermal pressure and Maxwellian electrons is carried out. The Korteweg-de Vries equation for the wave potential is derived via a reductive perturbation technique and its cnoidal wave solution is obtained. The effect of various relevant plasma parameters like ion pressure anisotropy and obliqueness of field on the characteristics of ion acoustic nonlinear periodic wave structures is investigated in detail. The present investigation could be useful in space and astrophysical plasma systems having ion pressure anisotropy, particularly, in the magnetosphere and near Earth magnetosheath.